2016
DOI: 10.15280/jlm.2016.6.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Habit of Eating Breakfast Is Associated with a Lower Risk of Hypertension

Abstract: BackgroundThe association between skipping breakfast and cardio-metabolic syndrome is well known. However, there are very few Korean studies about the habit of eating breakfast and hypertension. The present study aimed to investigate the relationship between the habit of eating breakfast and hypertension in a healthy Korean population.MethodsParticipants in the 2014 Korea National Health and Nutrition Examination Surveys (KNHANES) were enrolled for this study. Medical history, including hypertension, was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
1
20
1
1
Order By: Relevance
“…In contrast to our findings, Lee et al (2016) showed that skipping breakfast increases RBC concentrations. Another author showed that populations that consume breakfast more often have higher concentrations of iron in their serum (Min et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, Lee et al (2016) showed that skipping breakfast increases RBC concentrations. Another author showed that populations that consume breakfast more often have higher concentrations of iron in their serum (Min et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Another author showed that populations that consume breakfast more often have higher concentrations of iron in their serum (Min et al, 2011). Furthermore, the omission of breakfast leads to greater consumption of meat at dinner, which may explain the higher iron status (Lee et al, 2016). Other studies have demonstrated that omitting breakfast may have a negative impact on TCh, G, HDL-C, LDL-C, and TG concentrations, suggesting a greater risk of hypercholesterolemia and metabolic syndrome, hypertension, and type-2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between skipping breakfast and metabolic diseases remains a controversial issue, particularly in adults. Previous studies have demonstrated a positive association of not having breakfast with cardiometabolic risk factors, including obesity, hypertension, dyslipidemia, and hyperglycemia resulting from the metabolic syndrome in different countries, including Japan, Iran, and German, with different dietary patterns [ 25 , 26 , 27 , 28 ]. Inconsistent results might be related to no consideration of gender differences in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien es importante la calidad y la cantidad de alimentos consumidos, los horarios y tiempos de comida son parte del equilibrio diario. Aunque esto último no fue investigado en este trabajo, así lo demostró Sic Lee y cols., al evidenciar que las personas que consumen desayuno presentan un menor riesgo de desarrollar HTA 26 . A pesar de que numerosos estudios han identificado que el consumo de tabaco es un factor independiente para el desarrollo de HTA 11,27,28 , en este trabajo no se identificó una asociación entre estas variables en hombres, no obstante, en mujeres se identificó que el riesgo disminuía en fumadoras y exfumadoras.…”
Section: Discussionunclassified